KEHIDUPAN BERMAKNA PEREMPUAN YANG MENGALAMI KEKERASAN DALAM RUMAH TANGGA - Ariyanti, Ni Made Putri; Valentina, Tience Debora (Jurnal Psikologi Udayana, 2016)
Meaningful life occurs when an individual is able to give meaning to his life. To achieve a meaningful life, individuals go through a process of achieving a meaningful life that begins from the suffering stage, the stage of self-understanding, the discovery phase of the meaning of life, the meaning realization stage, and the stage of meaningful life. This study aimed to see a meaningful life of women who have experienced violence in the home. Domestic violence is any act against someone, especially women, which results in the emergence of physical, sexual, or psychological suffering, and /or negligence of households within the domestic sphere. This study used qualitative research with a phenomenological approach and the number of the respondents was three women experiencing domestic violence. The data used in this study were observation and interviews. The results of this study indicated that the process of achieving a meaningful life started from the stage of suffering, experiencing violence. The women who experienced violence were the ones found to have been divorced but reconciled with her husband, when women underwent violence they were not able to give meaning to their life in a positive way. When women were not able to give meaning to their life, they began praying and reading positive books that directed them to seek the meaning of life, namely children, religion, values, and expectations as the meaning of life which then directed them to change attitudes in the face of violence. Changing attitudes carried out by women are looking for help and choosing to separate from her husbands. After changing attitudes, women committed themselves to living a meaningful life that had been found to fulfill the meaning of life with work and developing skills. The women who had fulfilled the meaning of life were able to look at life more meaningful by generating belief, seeing violence as a trial and behind the trial is a lesson that can be learned and that it can ultimately bring happiness. Keywords: women, domestic violence, meaningful life